2020
DOI: 10.18632/aging.102888
|View full text |Cite
|
Sign up to set email alerts
|

Brain hemodynamic changes in amnestic mild cognitive impairment measured by pulsed arterial spin labeling

Abstract: We used pulsed arterial spin labeling (PASL) to investigate differences in cerebral blood flow (CBF) between 26 patients with amnestic mild cognitive impairment (aMCI) and 27 controls with normal cognition (NC). Hypoperfusion was observed in the right temporal pole of the middle temporal gyrus and the right inferior temporal gyrus in the aMCI compared with NC group. Interestingly, hyperperfusion was observed in the left temporal pole of the middle temporal gyrus, left superior temporal gyrus, bilateral precune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…A compensatory mechanism to maintain advanced neural activities by increasing blood oxygen and energy metabolism may also explain the relationship between gray matter hyperperfusion and mild cognitive impairment. 54 Supporting the hypothesis of a compensatory mechanism in the present study, activated flow during tasks has been reported to be lower in those doing well on cognitive tasks in normotensive individuals but with higher BP and BMI. 55,56 It is thus possible that, in our cohort, a higher CBF in treated hypertensive patients is associated with end-organ damages or compensatory mechanisms to maintain neural activities.…”
Section: Is Rmbp a Predictor Of Cognitive Performance Independently O...supporting
confidence: 89%
“…A compensatory mechanism to maintain advanced neural activities by increasing blood oxygen and energy metabolism may also explain the relationship between gray matter hyperperfusion and mild cognitive impairment. 54 Supporting the hypothesis of a compensatory mechanism in the present study, activated flow during tasks has been reported to be lower in those doing well on cognitive tasks in normotensive individuals but with higher BP and BMI. 55,56 It is thus possible that, in our cohort, a higher CBF in treated hypertensive patients is associated with end-organ damages or compensatory mechanisms to maintain neural activities.…”
Section: Is Rmbp a Predictor Of Cognitive Performance Independently O...supporting
confidence: 89%
“…Two articles described the same data set, one of which was excluded. Thirteen articles were finally included (Johnson et al, 2005 ; Xu et al, 2007 ; Alexopoulos et al, 2012 ; Wierenga et al, 2012 ; Kim et al, 2013 ; Ding et al, 2014 ; Okonkwo et al, 2014 ; Lv et al, 2015 ; Michels et al, 2016 ; Shokouhi et al, 2018 ; Duan et al, 2020 ; Wang et al, 2020 ; Shang et al, 2021 ), including 12 papers in English and one paper in Chinese, as shown in Figure 1 (literature screening flow chart).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of hyperperfusion in the LN in MCI patients may be related to compensatory mechanisms. The brain maintains higher neural activity by increasing blood oxygen and energy metabolism (Howarth, 2014 ; Wang et al, 2020 ). One study found that the mean CBF of the precuneus and postcentral gyrus in the aMCI group was positively correlated with cognitive level, but the result was not applicable in the control group (Wang et al, 2020 ), which laterally demonstrated the existence of compensatory mechanisms in MCI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A resting-state fMRI study showed synchronal abnormalities in the ITG and MTG of depressive patients who also have anxiety (Li et al, 2018). The ITG and MTG are also anoxia-sensitive regions, and hypoperfusion in the ITG and MTG was observed in amnestic mild cognitive impairment (aMCI), indicating impaired blood oxygen (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%